Difunctional self-supporting electrode composite material and preparation method and application thereof
By growing NiMo alloy on the surface of 3D foam nickel and coupling NiCoFe composites to form an alloy catalyst with one-dimensional nanowire structure, the existing electrolytic catalyst has solved the problems of high precious metal content, expensive and single functions, and achieved dual-function catalytic activity and low-cost electrocatalytic water decomposition efficiency.
Patent Information
- Application Number
- CN202411779770.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-05
- Publication Date
- 2025-03-18
AI Technical Summary
The existing electrolytic water catalysts have high precious metal content, are expensive and have a single function, making it difficult to effectively reduce the water decomposition energy barrier, affecting the electrocatalytic water decomposition efficiency.
By growing NiMo alloys in situ on the surface of 3D foam nickel and coupling NiCoFe composites, a two-step hydrothermal and one-step pyrolysis synthesis method is used to form an alloy catalyst with a one-dimensional nanowire structure, improving the intrinsic activity of the catalyst and exposing active sites.
Dual-function catalytic activity is achieved. As a full water-removing dual-function electrocatalyst, it can significantly increase the current density of hydrogen and oxygen at low overpotentials, reduce production costs, and simplify the catalyst production process.
Smart Images

Figure CN119638019A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of electrocatalysis and material preparation, and specifically relates to a dual-functional self-supporting electrode composite material and a preparation method and application thereof. Background Art
[0002] Hydrogen can release a lot of energy through chemical changes and is a good energy carrier. However, compared with non-renewable resources such as oil and natural gas, it cannot be mined and needs to be prepared before it can be used. Therefore, hydrogen energy is a secondary energy source and a renewable resource. Commonly used hydrogen production methods include: hydrogen production from fossil fuel reforming, biohydrogen production, and hydrogen production from water electrolysis. Among them, the hydrogen evolution reaction (HER) by water electrolysis can directly produce high-purity hydrogen using renewable clean energy (wind or solar energy) or electricity obtained from oversupplied power grids during off-peak hours. It is the cleanest and most economical way to produce the purest hydrogen. The water electrolysis process includes two half reactions, namely the hydrogen evolution reaction (HER) at the cathode and the oxygen evolution reaction (OER) at the anode. Both half reactions have slow kinetic processes. In particular, the OER process involves a complex four-electron transfer process, which seriously affects the efficiency of electrocatalytic water splitting. Therefore, the commercial water electrolysis process requires the use of cathode and anode electrocatalysts to improve the efficiency of electrocatalytic water splitting.
[0003] At present, commonly used electrocatalysts include Pt-based precious metal catalysts for cathodes and precious metal oxides such as Ru and Ir for anodes. However, the low abundance and high price of precious metals have seriously restricted the development of the water electrolysis industry. Therefore, the search for precious metal-like electrocatalytic active materials has attracted the attention of many researchers, especially the development of a bifunctional catalyst that can serve as both cathode and anode, which can greatly simplify the catalyst production process and reduce production costs.
[0004] Transition metal-based catalysts (Ni, Mo, Co, Fe, etc.) have become ideal substitutes for precious metal catalysts (Pt, Ru, Ir, etc.) due to their adjustable electronic structure and abundant crustal reserves. In particular, alloy catalysts composed of multiple metals have attracted more and more attention due to their easily adjustable electronic structure and high conductivity. At the same time, many studies have shown that the energy barrier of water decomposition can be further reduced and the catalytic activity of metal alloy catalysts can be optimized by rationally designing the structure of the catalyst and constructing heterogeneous interfaces.
[0005] Therefore, it is very necessary to develop a water electrolysis catalyst with simple preparation method, low price and excellent electrocatalytic activity. Summary of the invention
[0006] The purpose of the present invention is to provide a bifunctional self-supporting electrode composite material and a preparation method thereof. The present invention grows MoNi4 / MoO2 nanowires coupled with a ternary NiCoFe complex on a 3D nickel foam (NF) substrate, and improves the intrinsic activity of the catalyst through synergistic effects through in-situ coupling between metal alloys; at the same time, reasonable structural design is used to regulate the catalyst morphology through one-dimensional nanostructures, increase the exposed active sites, and finally design a bifunctional catalytic activity with excellent performance.
[0007] Another object of the present invention is to provide an application of a bifunctional self-supporting electrode composite material as a bifunctional electrocatalyst for overall water splitting.
[0008] The specific technical solutions of the present invention are as follows:
[0009] A method for preparing a bifunctional self-supporting electrode composite material comprises the following steps:
[0010] 1) adding the NiMoOx nanowires grown on the nickel foam into a mixed solution containing a nickel source, a cobalt source, an iron source and hexamethylenetetramine, and obtaining a precursor through a one-step hydrothermal reaction;
[0011] 2) Pyrolyzing the precursor of step 1) in a mixed atmosphere of hydrogen and argon to obtain a bifunctional self-supporting electrode composite material.
[0012] In step 1), the preparation method of the NiMoOx nanowires grown on the nickel foam is: placing the nickel foam in a solution containing a molybdenum source and a nickel source, and performing a hydrothermal reaction to obtain a NiMoOx nanowire precursor (NiMoOx / NF) on the nickel foam.
[0013] In the method for preparing NiMoOx nanowires grown on nickel foam, the nickel foam is pre-treated before use: the nickel foam (NF) is washed with ethanol and deionized water in sequence, and then ultrasonically treated in 2M hydrochloric acid for 10-15 minutes, taken out, washed and placed in a 60° C. oven for standby use;
[0014] In the preparation method of NiMoOx nanowires grown on nickel foam: in the solution containing a molybdenum source and a nickel source, the molar ratio of the molybdenum source to the nickel source is 1:2; the concentration of the molybdenum source is 0.025 mol / L; the molybdenum source is selected from a soluble molybdenum salt, preferably Na2MoO4·2H2O; the nickel source is selected from a soluble nickel salt, preferably Ni(NO3)2·6H2O; the solvent of the solution containing a molybdenum source and a nickel source is water, preferably deionized water.
[0015] In the method for preparing NiMoOx nanowires grown on nickel foam: the hydrothermal reaction is a reaction at 100-180°C for 6-12h;
[0016] Preferably, the preparation method of the NiMoOx nanowires grown on the nickel foam is: dissolving 1 mmol Na2MoO4·2H2O and 2 mmol Ni(NO3)2·6H2O in 40 mL of deionized water, then transferring the mixture into a polytetrafluoroethylene autoclave, placing the treated nickel foam therein, heating the mixture in a drying oven at 100-180°C for 6-12 h, and washing and drying to obtain a NiMoOx nanowire precursor (NiMoOx / NF) grown on the nickel foam.
[0017] In step 1), in the mixed solution containing a nickel source, a cobalt source, an iron source and hexamethylenetetramine, the molar ratio of the nickel source, the cobalt source, the iron source and the hexamethylenetetramine is 1-3:1-3:1-3:3-4;
[0018] In step 1), in the mixed solution containing a nickel source, a cobalt source, an iron source and hexamethylenetetramine, the concentration of the nickel source is 0.0125 to 0.0375 mol / L;
[0019] In step 1), the molar ratio of the molybdenum source for preparing the NiMoOx nanowires grown on the nickel foam to the iron source in the mixed solution containing the nickel source, the cobalt source, the iron source and hexamethylenetetramine is 1:1-3;
[0020] In step 1), in the mixed solution containing a nickel source, a cobalt source, an iron source and hexamethylenetetramine, the nickel source is selected from a soluble nickel salt, preferably Ni(NO3)2·6H2O or NiCl2·6H2O; the cobalt source is selected from a soluble cobalt salt, preferably Co(NO3)2·6H2O or CoCl2·6H2O; the iron source is selected from a soluble iron salt, preferably Fe(NO3)3·9H2O or FeCl3·6H2O;
[0021] In step 1), the hydrothermal reaction refers to: reacting at 80-100° C. for 1-2 hours under sealed conditions;
[0022] Preferably, step 1) is specifically as follows: 1-3 mmol Ni(NO3)2·6H2O, 1-3 mmol Co(NO3)2·6H2O, 1-3 mmol Fe(NO3)3·9H2O and 3-4 mmol hexamethylenetetramine HMTA are added to 80 mL of deionized water and dispersed uniformly by ultrasonication; the mixed solution is transferred to a 100 mL glass bottle, and the NiMoOx nanowires grown on nickel foam as a precursor are placed therein, heated to 80-100°C under sealed conditions for 1-2 hours, cooled naturally to room temperature, and then the yellow-brown product is taken out, washed and dried. The product is named NiCoFe-LDH@NiMoOx / NF.
[0023] In step 2), in the mixed atmosphere of hydrogen and argon, the volume percentage of hydrogen is 5%;
[0024] In step 2), the pyrolysis is: keeping warm at 400-800°C for 2h;
[0025] Step 2) is preferably: in a 5% hydrogen / argon mixed atmosphere, the temperature is raised to 400-800°C at a rate of 5°C / min, kept for 2 hours, and then naturally cooled to obtain a NiCoFe complex-coupled MoNi4 / MoO2 nanowire self-supporting catalyst, named NiCoFe-MoNi4 / MoO2 / NF.
[0026] The invention provides a dual-functional self-supporting electrode composite material, which is prepared by the above method. The dual-functional self-supporting electrode composite material has the following morphology: nanoparticles are distributed on the surface of one-dimensional nanowires.
[0027] The application of the bifunctional self-supporting electrode composite material provided by the present invention as a bifunctional electrocatalyst for water splitting. When used for HER, 10 mA cm -2 For OER, an overpotential of only 230 mV can achieve a current density of 50 mA cm -2 High current density. Excellent catalytic performance.
[0028] In view of the fact that the current electrolytic water catalysts are expensive and have a single function, the inventors found that Ni-Mo alloys and Fe, Co oxides can induce hydrogen and oxygen overflow, respectively, thereby promoting the transformation of hydrogen and oxygen intermediates to H2 and O2, respectively, wherein the unique two-phase interface between metal alloys and metal oxides plays a key role in regulating the electronic structure and improving the electrocatalytic activity. The present invention proposes a preparation method for developing a dual-activity electrolytic water catalyst with both HER and OER through alloying between cheap Ni, Mo, Co, and Fe elements. The method improves the intrinsic activity of the catalyst through synergistic benefits through in-situ coupling between metal alloys, and at the same time, uses reasonable structural design to regulate the catalyst morphology through one-dimensional nanostructures, increase the exposed active sites, and finally design a dual-functional catalytic activity with excellent performance.
[0029] In the present invention, NiMo alloy is in situ grown on the surface of 3D nickel foam and NiCoFe composite is coupled, and the in situ pyrolysis process enables full contact between the components to form a large number of heterogeneous interfaces, thereby synergistically improving the electrocatalytic activity of the catalyst; the present invention adopts a two-step hydrothermal and one-step pyrolysis synthesis method to simplify the synthesis process, and the catalyst exhibits bifunctional catalytic activity, which reduces the difficulty of industrialization and reduces the environmental pollution that may be generated during the production process; the unique nanoneedle structure of the invented catalyst provides a larger specific surface area for the reaction, exposes more abundant active sites, accelerates the mass transfer process, and improves the catalytic activity of the catalyst.
[0030] Compared with the prior art, the present invention in situ prepares a one-dimensional nanowire structured alloy catalyst on the surface of 3D nickel foam by two-step hydrothermal and one-step pyrolysis. The synthesis process includes using hexamethylenetetramine to in situ synthesize NiCoFe-LDH complex on the surface of NiMoOx nanowires at a relatively low temperature, and using it as an effective bifunctional electrocatalyst for overall water splitting. A strong synergistic effect is produced between the ternary NiCoFe complex and MoNi4 / MoO2, which improves the intrinsic activity of the catalyst. In addition, the NiCoFe complex improves the OER activity of the catalyst, so that the catalyst exhibits excellent overall water splitting activity. For HER, 10 mA cm can be obtained at an overpotential of 13 mV. -2 As for OER, an overpotential of only 230 mV can achieve a current density of 50 mA cm -2 of high current density. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 This is a SEM image of the catalyst surface during the implementation of Example 1 of the present invention;
[0032] Figure 2 HR-TEM spectrum of the catalyst NiCoFe-MoNi4 / MoO2 / NF obtained in Example 1;
[0033] Figure 3 Hydrogen evolution of the catalyst NiCoFe-MoNi4 / MoO2 / NF and the noble metal catalyst obtained in Example 1 ( Figure 3 a) and oxygen evolution ( Figure 3 LSV curve of (b);
[0034] Figure 4 The full water splitting performance curves of the catalyst NiCoFe-MoNi4 / MoO2 / NF and the noble metal catalyst obtained in Example 1. DETAILED DESCRIPTION
[0035] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0036] Unless otherwise specified, the test materials and reagents used in the following examples can be obtained from commercial sources.
[0037] If no specific techniques or conditions are specified in the examples, they can be carried out according to the techniques or conditions described in the literature in the art or according to the product instructions.
[0038] The precursor NiMoOx / NF used in the present invention is referenced in the literature [Self-Templated Fabrication of MoNi4 / MoO 3-x Nanorod Arrays with Dual Active Components for Highly Efficient Hydrogen Evolution, Adv. Mater. 29(39)(2020)1703311.] and slightly optimized the feeding ratio.
[0039] Example 1
[0040] A method for preparing a bifunctional self-supporting electrode composite material comprises the following steps:
[0041] 1) Cut the nickel foam into 2×5cm 2 The rectangular shape was washed with ethanol and water in sequence, and then ultrasonically treated in a 2M hydrochloric acid solution for 15 min, and then taken out and washed for later use;
[0042] 2) Weigh 0.242 g of sodium molybdate dihydrate (Na2MoO4·2H2O) and 0.582 g of nickel nitrate hexahydrate (Ni(NO3)2·6H2O) into a 50 mL small beaker, measure 40 mL of deionized water and pour it into the beaker, ultrasonically treat until the raw materials are completely dissolved to form a transparent solution, place the cleaned nickel foam obliquely in a 50 mL polytetrafluoroethylene reactor, pour in the prepared solution, and react in a 150 ° C oven for 6 h. After the reactor cools to room temperature, take out the nickel foam, rinse it with water and ethanol in turn, and then put it into a 55 ° C oven for drying. The prepared precursor is named NiMoOx / NF.
[0043] 3) Weigh 0.291g nickel nitrate hexahydrate (Ni(NO3)2·6H2O), 0.582g cobalt nitrate hexahydrate (Co(NO3)2·6H2O), 0.606g ferric nitrate nonahydrate (Fe(NO3)3·9H2O) and 0.4206g hexamethylenetetramine into a 100mL aluminum-capped glass bottle, add 80mL deionized water and sonicate until the solid is completely dissolved, place the prepared precursor NiMoOx / NF obliquely in the glass bottle, react in a 90°C oven under sealed conditions for 1h, take it out and cool it for 30min, rinse off the substances deposited on the surface with water and ethanol in turn, and then put it into a 55°C oven to dry, thus obtaining NiCoFe-LDH@NiMoOx / NF.
[0044] 4) The precursor NiCoFe-LDH@NiMoOx / NF obtained in step 3) was heated to 500°C at a rate of 5°C / min in a 5% hydrogen / argon mixed atmosphere, calcined for 2 hours, and then naturally cooled to obtain a NiCoFe complex-coupled MoNi4 / MoO2 nanowire self-supporting catalyst, named NiCoFe-MoNi4 / MoO2 / NF.
[0045] Figure 1 This is a SEM image of the catalyst surface during the implementation of Example 1 of the present invention, wherein Figure 1 a and d are the one-dimensional morphology structures of the precursor NiMoOx / NF. Figure 1 b and e are the morphology and structure of the precursor NiCoFe-LDH@NiMoOx / NF. Figure 1 Figures c and f show the morphological structures of the catalyst NiCoFe-MoNi4 / MoO2 / NF. It can be seen that the surface structure of the nanowires has changed significantly, indicating that the catalyst preparation results are in line with the expected design.
[0046] Figure 2 HR-TEM spectrum of the catalyst NiCoFe-MoNi4 / MoO2 / NF obtained in Example 1, Figure 2 In a and b, we can see that there are a large number of nanoparticles distributed on the surface of the one-dimensional nanowire, among which the brighter nanoparticles have an average size of about 2nm, while the darker NPs have a size of about 15nm. Figure 2 Figure c shows that the darker nanoparticle spacing is 0.185 and 0.208 nm, corresponding to the (310) and (121) planes of the MoNi4 alloy, respectively. Figure 2 Figures d and e show that the lattice spacing of the brighter nanoparticles is 0.469, 0.213, and 0.196 nm, which are attributed to the (111), (400), and (331) planes of NiCo2O4, Fe2MoO4, and CoFe alloy, respectively, which confirms that the NiCoFe composite (brighter nanoparticles) and MoNi4 species (darker nanoparticles) are successfully incorporated into the nanowire surface. The close contact between the two types of nanoparticles promotes charge exchange and improves the catalytic activity of the bifunctional catalyst.
[0047] Example 2
[0048] A method for preparing a bifunctional self-supporting electrode composite material comprises the following steps:
[0049] 1) Cut the nickel foam into 2×5cm 2 The rectangular shape was washed with ethanol and water in sequence, and then ultrasonically treated in a 2M hydrochloric acid solution for 15 min, and then taken out and washed for later use;
[0050] 2) Weigh 0.242 g of sodium molybdate dihydrate (Na2MoO4·2H2O) and 0.582 g of nickel nitrate hexahydrate (Ni(NO3)2·6H2O) into a 50 mL small beaker, measure 40 mL of deionized water and pour it into the beaker, ultrasonically treat until the raw materials are completely dissolved to form a transparent solution, place the cleaned nickel foam obliquely in a 50 mL polytetrafluoroethylene reactor, pour in the prepared solution, and react in a 150 ° C oven for 6 h. After the reactor cools to room temperature, take out the nickel foam, rinse it with water and ethanol in turn, and then put it into a 55 ° C oven for drying. The prepared precursor is named NiMoOx / NF.
[0051] 3) Weigh 0.378g of nickel nitrate hexahydrate (Ni(NO3)2·6H2O), 0.35g of cobalt nitrate hexahydrate (Co(NO3)2·6H2O), 0.424g of ferric nitrate nonahydrate (Fe(NO3)3·9H2O) and 0.4206g of hexamethylenetetramine in a 100mL aluminum-capped glass bottle, add 80mL of deionized water and sonicate until the solid is completely dissolved, place the prepared precursor NiMoOx / NF obliquely in the glass bottle, react in an oven at 100℃ for 1h, take it out and cool it for 30min, rinse off the substances deposited on the surface with water and ethanol in turn, and then put it in an oven at 55℃ to dry, so as to obtain NiCoFe-LDH@NiMoOx / NF.
[0052] 4) The precursor obtained in step 3) was heated to 600°C at a rate of 5°C / min in a 5% hydrogen / argon mixed atmosphere, calcined for 2 hours, and then naturally cooled to obtain a NiCoFe complex-coupled MoNi4 / MoO2 nanowire self-supporting catalyst, named NiCoFe-MoNi4 / MoO2 / NF.
[0053] Example 3
[0054] A method for preparing a bifunctional self-supporting electrode composite material comprises the following steps:
[0055] 1) Cut the nickel foam into 2×5cm 2 The rectangular shape was washed with ethanol and water in sequence, and then ultrasonically treated in a 2M hydrochloric acid solution for 15 min, and then taken out and washed for later use;
[0056] 2) Weigh 0.242 g of sodium molybdate dihydrate (Na2MoO4·2H2O) and 0.582 g of nickel nitrate hexahydrate (Ni(NO3)2·6H2O) into a 50 mL small beaker, measure 40 mL of deionized water and pour it into the beaker, ultrasonically treat until the raw materials are completely dissolved to form a transparent solution, place the cleaned nickel foam obliquely in a 50 mL polytetrafluoroethylene reactor, pour in the prepared solution, and react in a 150 ° C oven for 6 h. After the reactor cools to room temperature, take out the nickel foam, rinse it with water and ethanol in turn, and then put it into a 55 ° C oven for drying. The prepared precursor is named NiMoOx / NF.
[0057] 3) Weigh 0.237 g of nickel chloride hexahydrate (NiCl2·6H2O), 0.474 g of cobalt chloride hexahydrate (CoCl2·6H2O), 0.27 g of ferric chloride hexahydrate (FeCl3·6H2O) and 0.4206 g of hexamethylenetetramine into a 100 mL aluminum-capped glass bottle, add 80 mL of deionized water and sonicate until the solid is completely dissolved, place the prepared precursor NiMoOx / NF obliquely in the glass bottle, react in an oven at 80°C for 2 h, take it out and cool it for 30 min, rinse off the substances deposited on the surface with water and ethanol in turn, and then put it into an oven at 55°C to dry, thus obtaining NiCoFe-LDH@NiMoOx / NF.
[0058] 4) The precursor obtained in step 3) was heated to 800°C at a rate of 5°C / min in a 5% hydrogen / argon mixed atmosphere, calcined for 2 hours, and then naturally cooled to obtain a NiCoFe composite-coupled MoNi4 / MoO2 nanowire self-supporting catalyst, named NiCoFe-MoNi4 / MoO2 / NF.
[0059] Example 4
[0060] An application of a bifunctional self-supporting electrode composite material NiCoFe-MoNi4 / MoO2 / NF is specifically as follows: taking Example 1 as an example, the prepared composite catalyst NiCoFe-MoNi4 / MoO2 / NF is electrochemically tested in 1M KOH solution to draw an LSV curve.
[0061] All tests in the present invention were carried out on a Shanghai Chenhua CHI 760E electrochemical workstation, and the electrochemical performance of the catalyst was evaluated using a three-electrode system, wherein the working electrode was the prepared self-supporting catalyst (1×2 cm), the reference electrode was a Hg / HgO electrode, the counter electrode was a carbon rod, and the electrolyte was 1M KOH. The polarization curve of the catalyst was measured by linear sweep voltammetry (LSV), thereby studying the electrochemical hydrogen evolution (HER) and oxygen evolution (OER) performance of the catalyst.
[0062] Figure 3Hydrogen evolution of the catalyst NiCoFe-MoNi4 / MoO2 / NF and the noble metal catalyst obtained in Example 1 ( Figure 3 a) and oxygen evolution ( Figure 3 From the LSV curve in (b), we can see that the catalyst can exhibit catalytic activity that exceeds that of precious metals. Figure 3 As shown in Figure 2, the catalyst NiCoFe-MoNi4 / MoO2 / NF exhibits excellent catalytic performance for hydrogen and oxygen evolution under alkaline conditions, and only 13 mV is required to reach 10 mA cm for hydrogen evolution. -2 The current density of oxygen evolution reaction is only 230mV to reach 50mA·cm -2 of current density.
[0063] When the catalyst was used as both cathode and anode for the full water splitting test, Figure 4 The performance curves of the catalyst NiCoFe-MoNi4 / MoO2 / NF and the noble metal catalyst obtained in Example 1 are shown in FIG. Figure 4 As shown, only 1.51V is needed to reach 50mA·cm -2 The prepared catalyst participates in the catalytic reaction as both cathode and anode, and its performance exceeds the catalytic performance of commercially available precious metal electrodes, which has great commercial value.
[0064] The description of the above embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the protection scope of the present invention.
Claims
1. A method for preparing a bifunctional self-supporting electrode composite material, characterized in that: The preparation method comprises the following steps: 1) adding the NiMoOx nanowires grown on the nickel foam into a mixed solution containing a nickel source, a cobalt source, an iron source and hexamethylenetetramine, and obtaining a precursor through a one-step hydrothermal reaction; 2) Pyrolyzing the precursor of step 1) in a mixed atmosphere of hydrogen and argon to obtain a bifunctional self-supporting electrode composite material.
2. The preparation method according to claim 1, characterized in that: In step 1), the preparation method of the NiMoOx nanowires grown on the nickel foam is: placing the nickel foam in a solution containing a molybdenum source and a nickel source, and performing a hydrothermal reaction to obtain the NiMoOx nanowires on the nickel foam.
3. The preparation method according to claim 2, characterized in that: In the method for preparing NiMoOx nanowires grown on nickel foam: in the solution containing a molybdenum source and a nickel source, the molar ratio of the molybdenum source to the nickel source is 1:
2.
4. The preparation method according to claim 2, characterized in that: In the method for preparing NiMoOx nanowires grown on nickel foam, the hydrothermal reaction is a reaction at 100-180° C. for 6-12 hours.
5. The preparation method according to claim 1, characterized in that: In step 1), in the mixed solution containing nickel source, cobalt source, iron source and hexamethylenetetramine, the molar ratio of the nickel source, cobalt source, iron source and hexamethylenetetramine is 1-3:1-3:1-3:3-4.
6. The preparation method according to any one of claims 2 to 5, characterized in that: In step 1), the molar ratio of the molybdenum source for preparing the NiMoOx nanowires grown on the nickel foam to the iron source in the mixed solution containing the nickel source, the cobalt source, the iron source and hexamethylenetetramine is 1:1-3.
7. The preparation method according to claim 1, characterized in that: In step 1), the hydrothermal reaction refers to: reacting at 80-100° C. for 1-2 hours under sealed conditions.
8. The preparation method according to claim 1, characterized in that: In step 2), the pyrolysis is: Keep at 400-800℃ for 2h.
9. A bifunctional self-supporting electrode composite material prepared by the preparation method according to any one of claims 1 to 8.
10. An application of the bifunctional self-supporting electrode composite material according to claim 9, characterized in that: Application as a bifunctional electrocatalyst for overall water splitting.
Citation Information
Patent Citations
Preparation method and application of super-hydrophobic transition metal material / foam iron-nickel alloy structured catalyst
CN113578325A
Self-supporting non-noble metal electrocatalyst material as well as preparation method and application thereof
CN116180128A
Nickel-iron-cobalt trimetal nano array electrocatalyst, method and application of nickel-iron-cobalt trimetal nano array electrocatalyst in electrocatalytic oxidation of 5-hydroxymethylfurfural
CN118385603A
Iron cobalt nickel phosphide nanoflower electro-catalytic material and preparation method thereof
CN118516704A
Cited By
Alkaline electrolytic water hydrogen production electrode, preparation method and application
CN121321062A